1991
DOI: 10.1070/rc1991v060n10abeh001130
|View full text |Cite
|
Sign up to set email alerts
|

The verdazyl method for the study of the kinetics and mechanisms of the unimolecular heterolysis reactions of organic compounds

Abstract: A 6-dimensional grand unified theory with the compact space having the topology of a real projective plane, i.e., a 2-sphere with opposite points identified, is considered. The space is locally flat except for two conical singularities where the curvature is concentrated. One supersymmetry is preserved in the effective 4d theory. The unified gauge symmetry, for example SU(5) , is broken only by the non-trivial global topology. In contrast to the Hosotani mechanism, no adjoint Wilson-line modulus associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The salt effect depends on particular species (cationoid intermediate or covalent substrate) subject to the action of the salt ions or ion pairs. A study of the kinetics and mechanism of monomolecular heterolysis using the verdazyl method [8] showed that, when a salt acts on the covalent substrate, the reaction rate linearly increases with the salt concentration (normal salt effect, Fig. 1, line 1); when ÄÄÄÄÄÄÄÄÄÄÄÄ 1 For communication XXXVIII, see [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The salt effect depends on particular species (cationoid intermediate or covalent substrate) subject to the action of the salt ions or ion pairs. A study of the kinetics and mechanism of monomolecular heterolysis using the verdazyl method [8] showed that, when a salt acts on the covalent substrate, the reaction rate linearly increases with the salt concentration (normal salt effect, Fig. 1, line 1); when ÄÄÄÄÄÄÄÄÄÄÄÄ 1 For communication XXXVIII, see [1].…”
mentioning
confidence: 99%
“…To gain insight into this phenomenon, we studied the effect of LiClO 4 on the heterolysis of Ph 2 CHCl in g-butyrolactone. The kinetic experiments were performed at 35oC by the verdazyl method [8] using as internal indicators triphenylverdazyl radicals Z3Vd . : 1,3,5-triphenylverdazyl (H3Vd .…”
mentioning
confidence: 99%
“…This substituent, e.g., an alkyl group, is either present in the precursor or is introduced during the reaction. The accessibility of the initial formazans and the high stability of the verdazyl radicals have attracted and are still attracting the attention of chemists, biologists, and physicists [2][3][4][5][6][7][8][9][10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. New verdazyls [15-17, 19, 33] and their complexes with metals [16, 21-25, 27, 28, 30] and with π-acceptors [26,29,31,32] are regularly being synthesized, new characteristics of known verdazyls are being studied, and new aspects of their application are being sought, as in the creation of linear and helical polymers, organic magnetic materials, semiconductors, luminophores, etc.…”
Section: 234-tetrahydro-1245-tetrazinesmentioning
confidence: 99%
“…In the previous studies of this series [14,15], we examined by the verdazyl method [16] the effect of various salts on the rate of heterolysis of 3-bromocyclohexene IV in PhNO 2 . As internal triphenylverdazyl indicators ZVd .…”
mentioning
confidence: 99%
“…Proceeding with studies of salt effects in the heterolysis of bromide IV, we examined by the verdazyl method [16] . The reaction follows stoichiometric equation (3).…”
mentioning
confidence: 99%